Effect of Serratia sp. Application Rate on Frost Damage, Growth, and Yield of Potato (Solanum tuberosum L.) Under Field Conditions - Inggil Setyo Nugroho; Yuniel Melvanolo Zendrato; Maria Marina Herawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Frost damage poses a major constraint to potato (Solanum tuberosum L.) production in the Dieng Plateau, leading to significant yield loss. This study aimed to evaluate the effectiveness of Serratia sp. in mitigating the physical impacts of natural frost and improving plant growth and yield. The experiment was arranged in a Randomized Complete Block Design (RCBD) with four treatments of bacterial suspension application volume (density of 1 × 107 CFU/ml): control (0 ml/plant), 20 ml/plant, 40 ml/plant, and 60 ml/plant. A natural frost event occurred at a minimum temperature of -2 °C, causing minor damage. The results showed that the application of 60 ml/plant provided the best protection, with the lowest incidence of damage (<0.5%). The 40 and 60 ml/plant treatments consistently showed the highest plant height and leaf area, indicating accelerated vegetative recovery post-stress. In terms of yield, the 60 ml/plant treatment produced the highest tuber weight per plant (1,363 g). Further analysis confirmed that application volumes of 40 and 60 ml/plant significantly increased tuber size compared to the control. It was concluded that the application of Serratia sp. at a volume of 60 ml/plant was the best treatment in this study for stabilizing plant growth and maintaining potato productivity under low-temperature stress conditions in highland environments.